Pelatihan Keterampilan Programming Aplikasi Web Sederhana (Studi Kes Mahasiswa Di Jabatan Pendidikan Bahasa Melayu dan Teknologi Pendidikan) - Jehwae, Phaosan; Kamken, Daech; Paichamnan, Adul; Masila, Hunadee; Deama, Jirapan (Journal of Information System and Education Development, 2023)
Having web application programming skills allows you to develop and expand your knowledge of technology and freedom in creating Technological works. How to Create a web App is a complex process. However, there are some techniques that can help students learn and code in an efficient and fun way. Learn web application programming and practice through the web platform www.w3schools.com where you can practice coding and practice through examples available on the website. Content is easily accessible, content is updated, and it supports new technologies continuously. The content is updated in line with changes in programming languages and widespread technologies. so as to have the latest information. it is possible to learn anytime, anywhere, and using various devices such as desktops, tablets, or smartphones. There are many online resources available to learn web application programming with responsive and user-friendly designs.